Role of parents in fostering the practice of physical exercise and activities(Papel de los padres en el fomento de la práctica del ejercicio físico y las actividades) - Ali, Syed Kamaruzaman Syed; Tan, Pei Chian; Zulnaidi, Hutkemri (Universidad del Zulia, 2018)
This study aims to identify the role of parents in fostering physical exercise and activities amongst children via descriptive and inference statistics. Descriptive statistics included the use of percentage, mean and standard deviation. By contrast, inference statistics involved the use of t-test and one-way ANOVA. Results show a substantial difference in the role of parents in fostering the practice of physical exercise and activities based on race and academic qualification. In conclusion, parents should play a significant role in fostering the practice of a healthy lifestyle amongst their children, in which race is immaterial but the fostering applies to parents.